The Influence of Competency, Career Guidance and Self-Efficacy on Work Readiness - Safura Deswita Putri; Qristin Violinda; Ratih Hesty Utami P (Yayasan Al Ma'arif Dawuhan, 2025)
This research aims to analyze the influence of competency, career guidance, and self-efficacy on work readiness among 2020 PGRI Semarang University students. The study utilized primary data collected through questionnaires distributed via Google Forms to 100 respondents who were purposively selected. The sampling technique employed was non-probability sampling with a purposive sampling method, targeting students from PGRI University Semarang who enrolled in 2020. The variables examined in this research included work competency, career guidance, and selfefficacy as independent variables, and work readiness as the dependent variable. The findings revealed that there is a positive and significant influence of work competency on the work readiness of PGRI University Semarang students. This indicates that students with higher levels of competency are better prepared to face the demands of the job market. Similarly, career guidance was found to have a positive and significant impact on work readiness, underscoring the importance of structured and effective career support services in enhancing students’ employability. Furthermore, self-efficacy also demonstrated a positive and significant influence on work readiness, suggesting that students who believe in their abilities are more confident and prepared to enter the workforce. Overall, this research highlights the critical roles of competency, career guidance, and self-efficacy in shaping the work readiness of university students. The findings provide valuable insights for higher education institutions to develop targeted interventions aimed at improving these factors, thereby equipping students to successfully transition into the professional world.